Ata b. Ali el-Cuzcani’ye göre Ebu Hanife’nin Kelami görüşleri - Birinci, Züleyha (My University, 2007)
ATÂ b. AL el-CÛZCÂNÎ’YE GÖRE EBÛ HANÎFE’NN KELÂMÎ GÖRÜSLER slâm aleminde büyük bir çogunluk itikadî sahada Mâtürîdiyye mezhebine mensuptur. Ancak bu mezhebin alimleri yeterince tanınmamakta ve eserlerinin çogu da kütüphane raflarında yazmalar halinde bulunmaktadır. Bu eksikligi giderebilmek için özellikle son dönemlerde Mâtürîdiyye tarihi ile ilgili arastırmalar yogunlasmıstır. Mâtüridiyye’nin olusum ve gelisiminde mâm-ı Âzam Ebû Hanîfe’nin öncü bir rolü vardır. Buna binaen, bu çalısmada Ebû Hanîfe’ye nispet edilen el-Fıkhü’l-ekber adlı risalenin, Atâ b. Ali el-Cûzcânî’ye ait serhinin edisyon kritigi yapılmıstır. Böylelikle Mâtürîdîyye’ye baglı bir alime ait bir eserin edisyon kritigi yapılarak ilmî istifadeye sunulması ve Mâtürîdiyye tarihi açısından degerinin tespit edilmesi amaçlanmıstır. Bu çalısmada, bahsedilen eserin baska müelliflere nispet edilerek nesredildigi anlasılmıs, bunun üzerine eserin gerçek müellifinin ortaya çıkarılmasına çalısılmıstır. Arastırma sonunda, bu eserin Atâ b. Ali el-Cûzcânî’ye nispet edilmesinin isabetli olacagı sonucuna varılmıs ve eserdeki görüslerin tahlîline geçilmistir. Tahlil neticesinde bu serhin, Ebû Hanîfe’nin görüslerini Ehl-i Sünnet çizgisini takib eden mutedil bir yaklasımla ortaya koyan bir eser oldugu sonucuna varılmıstır.

EBU HANIFE’S THEOLOGIC IDEAS ACCORDING TO ATA b. ALI el- CUZCANI A great number of Islamic world, belong to the school of Maturidiyye in the belief aria. But scholars of this school are not known enough and many books of this school exist on the library shelfs as a manuscripts. To remove this deficiency, especially at the latest times, intensify researches about Maturidiyye history. Imam Azam Ebu Hanife has an advance guard role at formation and evolution of the school of Maturidiyye. Because of this, an edition critique of a commentary, which belongs to Ata b. Ali el-Cuzcani, on a text, is attiributed to Ebu Hanife which name is el-Fıkhü’l-ekber, is maden in this study. Herewith, to present a book, which belongs one of the Maturidi scholar, to the scientific benefit with making it’s edition critique and to fix it’s value in the Maturidiyye history, is aimed. In this study, it is understood that this book was published before, as attiributing it to another authors, whereupon the real author of this book is searched. At the and of the research it is gained that attiributing this book to Ata b. Ali el-Cuzcani is more true than the others and after this the ideas at this book is analysed. Eventually it is reasoned that this commentary is a book which presents subjects about Ebu Hanife’s ideas moderatly, with following Ehl-i Sunnet’s style
Keywords: İslam Dini; Kelam